1952
DOI: 10.1136/adc.27.131.82
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Abnormalities Associated with Pseudoxanthoma Elasticum

Abstract: Evidence has been presented by several authors that the skin condition known as pseudoxanthoma elasticum may be associated with widespread abnormalities of the blood vessels of the limbs and viscera (Sandbacka

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

1954
1954
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…Arteriography in one study (Carlborg et al, 1959) demonstrated arterial occlusive changes frequently in the lower limbs, whereas others (Goodman et al, 1963) found such changes more prominent in the upper extremities. Calcification of peripheral arteries had been reported as early as the ninth year of life (Wolff, Stokes and Schlesinger, 1952). There was no hypertension in the present patient although it has been described in 22-5 % of cases (Eddy and Farber, 1962).…”
Section: Discussionsupporting
confidence: 42%
“…Arteriography in one study (Carlborg et al, 1959) demonstrated arterial occlusive changes frequently in the lower limbs, whereas others (Goodman et al, 1963) found such changes more prominent in the upper extremities. Calcification of peripheral arteries had been reported as early as the ninth year of life (Wolff, Stokes and Schlesinger, 1952). There was no hypertension in the present patient although it has been described in 22-5 % of cases (Eddy and Farber, 1962).…”
Section: Discussionsupporting
confidence: 42%
“…Since granules in the periphery of elastic fibers have been reported in other conditions and are frequently interpreted as an indication of active elastogenesis,'''' ^^ we believe that the increased amounts of elastic fibers and peripheral granules in these elastic fibers represent increased elastogenesis in pseudoxanthoma elasticum. (2) In all except Case 4, the elastic fibers were electron lucent. The presence of a dense matrix in the elastic fibers in one case (Fig.…”
Section: Elastic Fiber Changesmentioning
confidence: 89%
“…Among possible causative factors of the elastic tissue degeneration, the authors dis cussed pathogenetic mechanisms similar to those in pseu doxanthoma elasticum. Reports of pulmonary vascular changes analogous to SP in pseudoxanthoma elastica have been published [24].…”
Section: Discussionmentioning
confidence: 99%